2547. Prioritizing Antimicrobial Resistance Learning Objectives Through a Modified, Two-Round, One-Day Delphi at a Multidisciplinary Conference - Budak, Jehan (Open Forum Infect Dis, 2019)
BACKGROUND: Antimicrobial resistance (AMR) is a global public health problem, but the learning needs of the medical profession on this topic are not well understood. The World Health Organization has called for better educational resources on AMR. Thus, we aimed to identify AMR learning objectives for physicians and medical trainees. METHODS: We designed a modified, two-round Delphi process to build consensus around these objectives, recruiting attendees at a one-day, multidisciplinary, international AMR symposium. Through review of the literature and discussion with experts in AMR, we generated an initial list of 17 objectives. We asked participants to rate the importance of including each objective in an AMR curriculum for physicians on a 5-point Likert scale, which ranged from “do not include” (1) to “very important to include” (5). Consensus for inclusion was predefined as ≥ 80% of participants rating the objective ≥ 4. RESULTS: The first round was completed by 30 participants, and the second by 21. Nobody declined to participate, but several people had to leave between rounds. Participants included physicians, researchers, graduate students, and a pharmacist, foundation manager, patient advocate, leader of an international financial institution, health administrator, and biomedical scientist. After the first round, 16 objectives met the consensus criteria, and participants suggested five additional topics. After the second round, 12 objectives met the consensus criteria (see Table 1). Objectives related to treatment of AMR most frequently met consensus criteria. Specific objectives with the highest consensus ratings were related to identifying infections not requiring antibiotics and recognizing the importance of using the narrowest spectrum antibiotic for the shortest period of time. CONCLUSION: We successfully employed a modified, one-day Delphi process at an international, multidisciplinary AMR symposium to build consensus among experts and stakeholders regarding key learning objectives for AMR. This technique may be useful for guideline committees and other taskforces in the Infectious Diseases community. Our generated list may be useful for those developing AMR training materials for medical students and physicians. [Image: see text] DISCLOSURES: All authors: No reported disclosures.